INTEGRATION OF CHARACTER VALUES IN INTRODUCTORY LEARNING IN THE PHYSICAL EDUCATION, HEALTH AND RECREATION STUDY PROGRAM - Arina Wanawati (CV. RADJA PUBLIKA, 2025)
This study aims to describe the form, strategy, and response of students to the integration of character values in the learning of the Introduction to Education course in the Penjaskesrek Study Program. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews, and documentation studies. The results of the study show that character values such as discipline, responsibility, cooperation, honesty, sportsmanship, and social care are integrated in learning both explicitly through RPS and implicitly through lecturer examples and participatory methods. The strategies used include reflective discussions, case studies, simulations, and affective assessments such as reflective journals and attitude observations. Students responded positively to the integration of character values, although some expected a more applicable form of implementation outside the classroom. These findings affirm the importance of character strengthening as an integral part of the learning process, especially in forming competent and moral physical educator candidates. This research contributes to the development of holistic learning and is oriented towards the formation of student personalities in higher education.